Ways of Strengthening Educational Partnership in the Physical Education of Primary School Students - Victoria LEȘCO; Gheorghe BRANIȘTE (ACROSS)
Strengthening the educational partnership between school and family is essential for ensuring the correct development of students. Constant communication; parental involvement in school life, so parents could get to know the school environment better and interact with teachers and other parents, counselling and support for parents, volunteering programs, assessment and feedback, mutual respect and trust, physical activity logs are some ways to strengthen this partnership. The school and the family must be based on mutual respect and trust. Teachers must respect parents' experience and values, and parents must trust teachers' skills and experience. Students are more likely to achieve learning success and develop harmoniously through collaboration and cooperation between school and family. At the same time, the school and parents can collaborate in planning the physical education program, considering the needs and preferences of the students. This may include consulting parents to better understand the level of physical activity at home and choosing activities and sports according to children's interests and abilities, to ensure a balanced profile well suited to their needs. Strengthening the school-family partnership in physical education can promote a healthy lifestyle and harmonious development of students. Communication, parent involvement, education and collaboration are essential for achieving this goal.